1982
DOI: 10.1161/01.cir.65.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Spasm of a normal or minimally narrowed coronary artery in the presence of severe fixed stenoses of the remaining vessels: clinical and angiographic observations.

Abstract: PATIENTS with stable angina occasionally experience symptomatic exacerbation. Their anginal pain occurs more frequently and can also appear at rest. This may represent worsening coronary artery disease, and if the angina is unresponsive to medical therapy, coronary angiography is considered. If severe, operable lesions are found, coronary bypass surgery is then considered,We present four patients in whom this sequence occurred. However, most of their symptoms were apparently due to spasm of a normal or minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The results reported here support prior observation 5,6 that fixed narrowing of the coronary artery does not always produce myocardial ischemia. Prinzmetal et al 7 first described the syndrome of variant angina and they suggested that the transient ST-segment elevation is due to temporary total occlusion of a diseased coronary artery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results reported here support prior observation 5,6 that fixed narrowing of the coronary artery does not always produce myocardial ischemia. Prinzmetal et al 7 first described the syndrome of variant angina and they suggested that the transient ST-segment elevation is due to temporary total occlusion of a diseased coronary artery.…”
Section: Discussionsupporting
confidence: 91%
“…Mautner 5 reported that seven patients with significant fixed occlusive coronary artery disease had coronary artery spasm in a "normal" vessel, of which six had spontaneous spasm during catheterization and one ergonovine-induced spasm. Mercurio et al 6 reported four patients with medically refractory rest angina. During cardiac catheterization, intravenous ergonovine reproduced the chest pain and induced coronary artery spasm in a normal or minimally diseased vessel, despite the presence of fixed stenosis in the remaining vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six patients had one or more episodes of rest angina and four sustained recent myocardial infarction. Mercurio et a1 reported four patients with medically refractory rest angina [2]. During cardiac catheterization intravenous ergonovine maleate reproduced the chest pain and induced coronary vasospasm in a normal or minimally diseased vessel, despite the presence of fixed stenosis in the remaining vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that endothelial dysfunction of coronary arteries plays a pivotal role in the development of CS [5,6], and CS occurs in both patients with normal coronary angiograms and also in those with atherosclerotic coronary stenosis [7][8][9]. For the differential diagnosis of CS, provocation tests using acetylcholine (ACh) or ergonovine are usually performed, and intracoronary injection of ACh is reported to be sensitive (N90%) and reliable for the diagnosis of CS [10,11].…”
Section: Introductionmentioning
confidence: 99%